Uncovering Key Transcription Factors Driving Chilling Stress Tolerance in Rice Germination - Vívian Ebeling Viana; Camila Pegoraro; Viviane Kopp da Luz; Antonio Costa de Oliveira; Luciano Carlos da Maia (DNA)
Background: Rice, one of the main foods in Brazil and the world, is sensitive to chilling (0–15 °C), especially in the germination and reproductive stages. Chilling causes delayed germination and affects coleoptile elongation at the S3 stage (needlepoint), causing poor plant establishment, stunted growth, and non-vigorous plants, also impacting weed management. Elucidating the mechanisms responsible for resilience under cold conditions helps the development of tolerant cultivars. Transcription factors (TFs) act in stress response signaling, making them indispensable in the tolerance mechanism. Objective: Thus, this study aimed to identify and characterize the expression profile of transcription factors in the response to chilling stress in rice at the germination stage. Methods: To determine the transcriptional profile of 2408 genes belonging to 56 TF families, RNAseq was performed on the shoot tissue of seedlings of Oro (chilling-tolerant) and Tio Taka (chilling-sensitive) genotypes grown under control conditions (25 °C) and chilling stress (13 °C) until the S3 stage. Results: Of the total genes analyzed, 22% showed significant differential expression in the analyzed cultivars. There were 117 genes that showed significant differential expression in the tolerant cultivar, 60 of which were downregulated and 57 upregulated. In the sensitive cultivar, 248 genes had a significant differential expression, of which 98 genes were downregulated and 150 genes were upregulated. A total of 170 genes encoding TFs were commonly and significantly differentially expressed in the tolerant and sensitive genotypes. Conclusions: Here, we revealed potential new targets involved in the regulation of chilling stress in rice at the S3 stage.